DIMENSIONS OF LEADERSHIP IN THE PROCESS OF INTERNATIONALIZATION OF HIGHER EDUCATIONAL INSTITUTIONS - Malaniuk, Nazarii (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article considers scientific approaches to the formation of educational leadership, which made it possible to propose the author's vision of the dimensions of leadership of a higher education institution in the process of ensuring effective international integration of the institution. It is shown that the internationalization of education provides a higher education institution and all stakeholders with a number of advantages and opportunities, at the same time it carries risks and challenges, and can also have negative consequences to a certain extent, which can be predicted and prevented thanks to professional management. In such conditions, a special role is assigned to the leader and his team, who must flexibly respond to all challenges and achieve the set strategic goals of the educational institution. An approach to the formation of the leadership system of a higher education institution is developed, emphasizing the need for systematic and comprehensive implementation of internationalization. It is proposed to consider the leadership of a higher education institution from the position of ensuring internationalization in five dimensions: structural, political, symbolic, academic and managerial. It is determined that it is the leader who should form a global vision of the higher education institution in the team and the entire staff of the higher education institution, which combines academic quality, cultural diversity and social responsibility, and is understandable both to internal participants in the educational process and to external, including international partners. The task of the leader is formed from the position of the symbolic dimension. Within the framework of revealing the managerial dimension of leadership, the transition from the traditional perception of the employee to the modern one is demonstrated. Academic leadership is presented as the ability of managers in the field of higher education (rectors, deans, heads of departments, scientific coordinators) to form a vision, values ​​and culture that contribute to the quality of education, scientific achievements and international reputation of the higher education institution. We systematize the conducted research in the form of a profile of the competencies of the HEI leader from the position of the internationalization of education and science.